Effects of ginger supplementation in individuals with mild to moderate joint pain I: ratings of pain, functional capacity, and markers of inflammation - Jacob Broeckel; Landry Estes; Megan Leonard; Broderick Dickerson; Drew E. Gonzalez; Martin Purpura; Ralf Jäger; Ryan Sowinski; Christopher J. Rasmussen; Richard B. Kreider (Journal of the International Society of Sports Nutrition)
Background Ginger contains gingerols, shogaols, paradols, gingerdiones, and terpenes which have shown to display anti-inflammatory properties and inhibit pain receptors. For this reason, ginger has been marketed as a natural ingredient for joint health. The purpose of this study was to determine whether a specialized ginger extract effects pain perception, functional capacity and markers of inflammation.Methods 30 men and women (56.0 ± 9.0 years, 164.4 ± 14 cm, 86.5 ± 20.9 kg, 31.0 ± 7.5 kg/m2) with a history of mild to severe joint and muscle pain and inflammation participated in a randomized, placebo-controlled, parallel-arm, intervention trial. Participants donated fasting blood, completed questionnaires, rated pain in the thighs to standardized pressure, and then completed 3 × 10 repetitions of squats/deep knee bends while holding 30% of body mass on days 0, 30, and 56 of supplementation. Participants repeated tests after 2-days of recovery following each testing session. Blood samples were evaluated for markers of inflammation. Muscle soreness was assessed using an algometer at three locations on the thigh. The WOMAC Osteoarthritis Global Index and Lequesne Functional Index (LEQ) Questionnaires were utilized to assess perception of pain and functional capacity. Participants were matched by age, sex, and body mass for double-blind and to ingest 125 mg/d of a placebo or ginger (GingerT3®, Specnova LLC, Tysons Corner, Virginia), standardized to contain 10% total gingerols and no more than 3% total shogaols) for 58 days. Data were analyzed using the general linear model (GLM) analysis of variance with repeated measures, mean changes from baseline with 95% confidence intervals, and chi-squared analysis.Results There was evidence that ginger supplementation: 1.) attenuated perceptions of muscle pain in the vastus medialis (Day 2: χ2 p = 0.087); 2.) reported less pain from sitting (Day 2: χ2 p = 0.02), while nocturnal pain (Day 32: χ2 p = 0.075, Day 58: (χ2 p = 0.097), weight bearing pain (Day 32: χ2 p = 0.058), physical functioning of performing heavy duties (Day 32: χ2 p = 0.100), and physical functioning of performing light duties (Day 2: χ2 p = 0.064) on WOMAC questions; 3.) experienced significant reductions in WOMAC overall ratings of pain, stiffness, physical function, and total score values, particularly in 48-hour follow-up measures; 4.) reported less pain during nighttime bed rest (Day 2: χ2 p = 0.065; Day 32: χ2 p = 0.032) and when going up and down stairs (Day 32: χ2 p = 0.097) from the LEQ; and, 5.) promoted significant differences over time and/or between groups in IL-β, IL-5, IL-6, IL-8, INF-γ, TNF-α, and high sensitivity C-reactive Protein at various points during the study.Conclusion Ginger supplementation promotes some favorable effects on exercise-induced perceptions of pain, functional capacity, and inflammatory markers in men and women who have mild to moderate muscle and joint pain.Registered clinical trial #ISRCTN74292348.